Novel Planar Electromagnetic Sensors: Modeling and Performance Evaluation - Subhas C. Mukhopadhyay (Sensors, 2005)
High performance planar electromagnetic sensors, their modeling and a fewapplications have been reported in this paper. The researches employing planar typeelectromagnetic sensors have started quite a few years back with the initial emphasis on theinspection of defects on printed circuit board. The use of the planar type sensing system hasbeen extended for the evaluation of near-surface material properties such as conductivity,permittivity, permeability etc and can also be used for the inspection of defects in the nearsurfaceof materials. Recently the sensor has been used for the inspection of quality ofsaxophone reeds and dairy products. The electromagnetic responses of planar interdigitalsensors with pork meats have been investigated.